Impact of Credit Risk on the Value of Universal Banks in Ghana - Bempong Adjei Daniel (KNUST, 2023)
Dissertation submitted to the Department of Accounting and Finance of the School of Business, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the award of the Master of Science Degree in Accounting and Finance